2020
DOI: 10.1200/jco.19.02005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Feasibility Trial of a Novel Strategy of Facilitated Cascade Genetic Testing Using Telephone Counseling

Abstract: PURPOSE A powerful consequence of detecting cancer-associated pathogenic variants is the ability to test at-risk relatives (ARRs), termed cascade testing. However, historical studies suggest cascade testing uptake of 30% or less. Here, we tested the feasibility of a novel, streamlined method of cascade testing using telephone genetic counseling and mailed saliva-based genetic testing. PATIENTS AND METHODS Probands with newly diagnosed cancer-associated pathogenic variants were offered facilitated cascade test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 27 publications
0
73
2
Order By: Relevance
“…Despite the high pretest probability of detecting a P/LP variant, the relatively low cost and the straightforward interpretation (without VUS), uptake of cascade testing in family members at risk of a cancer predisposition has typically been suboptimal. Previous studies in adult cancer predisposition have generally found that approximately half of at-risk first-degree relatives undergo cascade testing 33 , with more recent initiatives investigating practices to identify and reduce burdens on family members to increase uptake 16,[34][35][36] . Uptake in our cohort was similarly low, although variable based on penetrance of the variant as well as the gene itself (that is, a low cascade testing rate for NF1 is unsurprising given that the diagnosis or absence of a diagnosis can typically be made clinically in relatives).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high pretest probability of detecting a P/LP variant, the relatively low cost and the straightforward interpretation (without VUS), uptake of cascade testing in family members at risk of a cancer predisposition has typically been suboptimal. Previous studies in adult cancer predisposition have generally found that approximately half of at-risk first-degree relatives undergo cascade testing 33 , with more recent initiatives investigating practices to identify and reduce burdens on family members to increase uptake 16,[34][35][36] . Uptake in our cohort was similarly low, although variable based on penetrance of the variant as well as the gene itself (that is, a low cascade testing rate for NF1 is unsurprising given that the diagnosis or absence of a diagnosis can typically be made clinically in relatives).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of outcomes was possible only for 13 studies, and not all of them had assessed family communication of test results and/or cascade genetic testing of relatives as a primary outcome. Our literature search identified serendipitously additional papers describing the development of relevant interventions [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. However, none of them had been rigorously tested with an RCT, indicating that the scientific field is still in development.…”
Section: Discussionmentioning
confidence: 99%
“…However, removing this barrier does not guarantee successful cascading of blood relatives due to the resources needed to identify, contact, and counsel them. Additional measures, such as mailing of saliva kits [ 64 ] and family-based telephone or web-based counseling, hold promise to enhance cascade genetic testing and improve individual and population health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As one study shows, 68.4% of minority women completed testing after a telephone session, as compared with 87% completion within non-Hispanic white participants (Butrick et al, 2015). In other studies that have taken measures to lower barriers to sample collection, however, increased testing uptake among participants after telephone genetic counseling is reported (Frey et al, 2020).…”
Section: Genetic Counseling and Telehealthmentioning
confidence: 96%